Agile cyber defense: Enhancing digital substation resilience with SDN-based smart switching - Sultan H. Almotiri (PLoS ONE, 2025)
This paper provides an evaluation methodology and prototyped and tested a virtual Intelligent Electronic Device (vIED) for digital substations in a Real Time (RT) simulation. Based on the IEC 61850 standard and virtualization technology, the proposed framework aims to enhance protection, automation, and control systems for application in today’s substations. A new and very specific method of testing was conceived and used as an instrument for verifying the given framework and its potential based on different methods of communications, scalability, and functionality options. The analysis also examines the effectiveness of the SDCommNet for vIED frameworks about operational network re-scaling capacity, besides testing the impact of nominal and transient data traffic on the global performance of the system. Empirical findings demonstrate that the vIED framework always meets essential system characteristics, such as response time and network transfer latency, irrespective of configurations. Such findings act as a perfect foundation for future development of design and testing protocols for the virtualization of substation systems.